2020
DOI: 10.1167/iovs.61.6.28
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MST4 Underlies a Novel Inhibitory Role of MicroRNA Let-7a in the Progression of Retinoblastoma

Abstract: of MST4 underlies a novel inhibitory role of microRNA let-7a in the progression of retinoblastoma. Invest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Similarly, some factors showed upregulation at day 31 during the peak of pro-angiogenic activity, with decreased expression by day 35. These included lamin A 42 (LMNA; ↑d31), L-lactate dehydrogenase A chain [43][44][45] (LDHA; ↑d31), and serine/ threonine protein kinase 26 46 (STK26 or MST4; ↑d31) (Text Data S2 †).…”
Section: Key Members Of the Vegf Signaling Pathway Agree With Observe...mentioning
confidence: 99%
“…Similarly, some factors showed upregulation at day 31 during the peak of pro-angiogenic activity, with decreased expression by day 35. These included lamin A 42 (LMNA; ↑d31), L-lactate dehydrogenase A chain [43][44][45] (LDHA; ↑d31), and serine/ threonine protein kinase 26 46 (STK26 or MST4; ↑d31) (Text Data S2 †).…”
Section: Key Members Of the Vegf Signaling Pathway Agree With Observe...mentioning
confidence: 99%
“…10 Additionally, let-7a inhibits angiogenesis in retinoblastoma (RB) by silencing MST4 and inhibiting the MAPK signaling pathway. 11 An et al showed that MST4, via a nonclassical branch of the Hippo pathway, limits the activation of the stress-induced transcriptional coactivator YAP during gastric tumorigenesis. 12 However, the role of MST4 in OS is unclear, which prompted us to explore the role of MST4 in OS proliferation and to provide a theoretical basis for finding new breakthroughs in the treatment of OS.…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer, overexpression of MST4 can promote the proliferation of cancer cells in vitro and increase tumorigenicity in vivo, facilitating the growth of prostate cancer 10 . Additionally, let‐7a inhibits angiogenesis in retinoblastoma (RB) by silencing MST4 and inhibiting the MAPK signaling pathway 11 . An et al showed that MST4, via a nonclassical branch of the Hippo pathway, limits the activation of the stress‐induced transcriptional coactivator YAP during gastric tumorigenesis 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation